A novel study on the effectiveness of bioflocculant-producing bacteria Bacillus enclensis, isolated from biofloc-based system as a biodegrader in microplastic pollution. (December 2022) - Ahmad Shukri, Zuhayra Nasrin; Che Engku Chik, Che Engku Noramalina; Hossain, Shahadat; Othman, Rohisyamuddin; Endut, Azizah; Lananan, Fathurrahman; Terkula, Iber Benedict; Kamaruzzan, Amyra Suryatie; Abdul Rahim, Ahmad Ideris; Draman, Ahmad Shuhaimi; Kasan, Nor Azman
Highlights: B.enclensis was identified as bioflocculant-producing bacteria based on morphological and flocculating activity. Bioflocculant-producing bacteria, B. enclensis yielded 93% of flocculation efficiency. Microplastics was incubated with B. enclensis, changes in physical and chemical properties were observed by SEM and FTIR. The microplastics served as the sole source of carbon for the bacterial culture that was grown in Mineral Salt Medium. Inoculation of B. enclensis with microplastics provide eco-friendly treatment for microplastic pollution in aquaculture.